(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
The planned obsolescence of electronic equipment, coupled with the encouragement of consumerism for these items, has contributed to the increasing generation of electronic waste. This poses risks to human and environmental health, mainly due to the presence of heavy metals in its composition. However, many small locations do not have educational programs and collection points for this material. Thus, the aim was to describe an experience report on the environmental education and electronic waste activities developed with elementary school students from two municipal schools located in the city of Montanhas/RN. For this, a workshop was held with 08 classes (6th to 9th grade - 164 students in total). At first, concepts of selective collection were addressed, how to separate dry waste using the color separation of selective collection, concepts of electronic waste and suitable places for its disposal, as well as the impacts they cause to the environment. In the second moment, an educational game was carried out through a Quiz with questions and answers on the theme. At the end of the activity, it was possible to perceive that the students had rich notions about the environment.